Dampak Pengetahuan Wajib Pajak Terhadap Kepatuhan Wajib Pajak Dengan Kualitas Laporan Keuangan Sebagai Variabel Moderating (Studi Empiris pada UMKM di Kota Malang) - Nengnis Uswatul Kasanah; Nur Diana; Umi Nandiroh (Universitas Islam Malang, 2023)
This study aims to analyze the impact of taxpayer knowledge on taxpayer compliance with the quality of financial statements as a moderating variable in Micro, Small and Medium Enterprises in Malang city. Sampling in this study used purposive sampling techniques using the slovin formula. This study used primary data by distributing questionnaires by compiling a list of questions or written statements to 73 Micro, Small and Medium Enterprises registered at the Malang City Cooperative and Industry Office including owners or managers who met the criteria of researchers. The results of this study show: 1) Taxpayer knowledge has a significant influence and has a positive effect on taxpayer compliance, 2) The interaction of taxpayer knowledge with the quality of financial statements on taxpayer compliance has a significant influence and has a negative effect. The influence of moderation variables, namely the quality of financial statements, can explain strongly the relationship between the three variables. Keywords : Taxpayer knowledge, taxpayer compliance, quality of financial statements